Bilateral adrenal hyperplasia; a common cause of drug-refractory hypertension yet amenable to medical treatment - Kamel, El-Reshaid; Al-Bader, Shaikha (Journal of Drug Delivery and Therapeutics, 2020)
Over the past 4 and 1/2 years, a total of 97 patients had hypertension yet lacked clinical, laboratory and radiological evidence of renal, renovascular and endocrine disease were investigated for A/R ratio.  High A/R was detected in 30 patients.  Five patients had unilateral adrenal adenoma and 1 had cancer while 24 patients (24.7%) had bilateral enlargements indicating bilateral adrenal hyperplasia (BAH).  Our study has shown that BAH is: (a) easily diagnosed with a combination of A/R ratio and CT scan of the adrenal gland, (b) responsible for 24.7% of hypertension cases, (c) associated with moderate to severe hypertension that may require 2-4 antihypertensives, (d) associated with hypokalemia in only in 54% of the cases, (e) not controlled with a single daily dose of Spironolactone (S) and ½ the cases require 50 mg/day.   Moreover, it has shown that S treatment was not associated with significant hyperkalemia yet gynecomastia and erectile dysfunction were common side effects.  Interestingly; and despite normalization of A/R ratio, most patients continue to require antihypertensive drugs though the number and dosage were less.  The latter phenomenon was more evident in those with higher initial A/R ratio and longer duration of hypertension.  Nephroangiosclerosis is the most plausible explanation for it.  In conclusion; BAH is not a rare disease and should be considered in cases of refractory hypertension. Keywords: Aldosterone, Aldosterone/Renin ratio, hypertension, Spironolactone.